THE EFFECT OF USING EDUCATIONAL GAMES ON THE STUDENTS’ ACHIEVEMENT IN ENGLISH LANGUAGE FOR THE PRIMARY LEVEL CHILDREN - Xoliqova Dildora; Umaraliyeva Munojatxon (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
This piece of writing examines the significance of incorporating educational games in foreign language teaching and the advantages of implementing gamification methods in the classroom. Additionally, it proposes some game options that can be utilized for instructional purposes